Unsteady flow simulation using unstructured meshes - Hassan, O.; Probert, E.J.; Morgan, K.; Weatherill, N.P. (Computer methods in applied mechanics and engineering, 2000)
Transient flows involving moving boundaries are more difficult to simulate, as the geometry of the computational domain changes with time. Regardless of the changes occurring in the solution, the mesh must be modified during the computation in order to accommodate the changes in the geometry. Although the literature on this subject describes a number of different approaches for handling this type of problem, the approach followed in this paper is to use unstructured mesh methods. We consider, initially, the simulation of inviscid two-dimensional transient flows involving moving bodies, employing an extension of adaptivity procedures which have been successfully used for steady state problems with the error estimation procedure coupled to an automatic triangular mesh generator. This approach is extended to produce a three-dimensional capability using tetrahedral meshes. A number of examples are included to illustrate the numerical performance of these methods.